Factors Associated with K4 Service Utilization by Pregnant Women in the Working Area of Kambaniru Health Center East Sumba District - Kartini Pekabanda; Yublina Rohi (Poltekkes Kemenkes Kupang, 2018)
Background: In 2014-2015 there was decline coverage of K4 in East Sumba regency and it was only reached 44.7%, it was far from the target of 85%. Preliminary study results show that pregnant women do not know the benefits of k4, access to remote health care, expensive transfortasi cost. The purpose of this study is to determine the factors a associated with the utilization of k4 services by pregnant women ini puskesmas kambaniru. Methods: This analytic observational study uses survey methods with a cross-sectional design. The Subjects of the study were 84 pregnant women were who were selected by clustered random sampling at the health center and village. Data were collected by interviews using a structured questionnaire. Bivariate analysis is tested by the chi square test and multivariate logistic regression. Results: The research results showed that 59.5% of respondents did not utilize K4, 61.9% was lack of knowledge, 60.7% was hard to reach health center, 57.1% did not have costs, 57.1% had low perception of K4. There is a positive relationship between knowledge (p = 0.001), ease of reaching health center (p = 0.02), the availability of cost (p = 0.001), perception of needs (p = 0.02) with the use of K4. Conclusion: There is a relationship between knowledge, ease o reaching puskesmas, availability o cost, perception to requirement with utilization of service K4.